Evaluation of Euglena gracilis 815 as a New Candidate for Biodiesel Production - Chen, Zixi; Chen, Yehua; Zhang, Hua; Qin, Huan; He, Jiayi; Zheng, Zezhou; Zhao, Liqing; Lei, Anping; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2022)
Euglena comprises over 200 species, of which Euglena gracilis is a model organism with a relatively high fatty acid content, making it an excellent potential source of biodiesel. This study isolated and characterized a new strain named E. gracilis 815. E. gracilis 815 cells were cultivated under light and dark conditions, with either ethanol or glucose as an external carbon source and an autotrophic medium as control. To achieve maximum active substances within a short period i.e., 6 days, the effects of the light condition and carbon source on the accumulation of bioactive ingredients of E. gracilis 815 were explored, especially fatty acids. In comparison with the industrially used E. gracilis Z strain, E. gracilis 815 exhibited high adaptability to different carbon sources and light conditions, with a comparable biomass and lipid yield. The content and composition of fatty acids of E. gracilis 815 were further determined to assess its potential for biodiesel use. Results suggested that E. gracilis 815 has biodiesel potential under glucose addition in dark culture conditions and could be a promising source for producing unsaturated fatty acids. Therefore, E. gracilis 815 is a candidate for short-chain jet fuel, with prospects for a wide variety of applications.